Reagent Distribution and Micellar Catalysis of 4-Substituted Benzenesulfonyl Chloride Reactions - A. Al-Lohedan, Hamad (Asian Journal of Chemistry, 2010)
Reactions of OH–1 and HCO2– with 4-nitro, 4-bromo,. and 4-methyl-benzenesulfonyl chloride derivatives have been examined in solutions of cetyltrimethylammonium chloride, hydroxide and formate. Rate effects were analyzed quantitatively in terms of distribution of reactant between water and micellar pseudophases. Second-order rate constants at the micellar surface are very similar to that in water for reactions with HCO2Na while for reactions with OH– the second-order rate constants at the micellar surface is considerably smaller than that in water.